Calculation of the Breit–Rosenthal Effect in Bi I - Tarje Arntzen Røger; Jonas R. Persson (Atoms)
Corrections to the measured nuclear magnetic moments obtained from hyperfine structure measurements include the Breit–Rosenthal effect. In this paper, we present results from calculations on Bi using the GRASP2018 code. The results indicate that the Breit–Rosenthal effect is on the order of 0.1<semantics>%fm−2</semantics>, the same order of magnitude as neighbouring elements, while some atomic states may have one order of magnitude smaller values. The ground state <semantics>6p3 <mmultiscripts>S3/2o<mprescripts></mprescripts><none></none>4</mmultiscripts></semantics> is more sensitive to the Breit–Rosenthal effect, and hence the hyperfine anomaly, with a value of −0.25<semantics>%fm−2</semantics>.